1984
DOI: 10.1017/s0022172400064901
|View full text |Cite
|
Sign up to set email alerts
|

Legionella pneumophilain aerosols from shower baths

Abstract: Routine examination of the water system in an establishment where showers were used by staff after work or leisure activities revealed the presence of Legionella pneumophila. Descaling and steaming cleared the system but six months later recolonization was found to have occurred. L. pneumophila was isolated from air samples collected in the shower room whilst the shower was in operation. No clinical cases have occurred. Serological examination of those using the showers throughout the six month period together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 25 publications
5
25
0
1
Order By: Relevance
“…Ninety percent of L. pneumophila recovered were in aerosols between 1 and 5 μm in diameter, sizes capable of alveolar deposition. 154 Similar to other studies, when Dennis et al 155 examined L. pneumophila aerosol generation by plumbing in bathrooms, they found very low concentrations (0.27-0.44 CFU m -3 ) of bacteria in the air during the first 15 minutes of showering and no airborne Legionella during 15 and 30 minutes of showering, even though concentrations of L. pneumophila in the water were approximately 10 3 CFU L -3 . At a breathing rate of 12 L min -1 , over 4 hours of showering would be required to inhale just one “viable” Legionella cell (although the researchers likely meant to use the term “culturable” since viable but non-culturable (VBNC) cells were not distinguished in their study).…”
Section: Introductionsupporting
confidence: 79%
“…Ninety percent of L. pneumophila recovered were in aerosols between 1 and 5 μm in diameter, sizes capable of alveolar deposition. 154 Similar to other studies, when Dennis et al 155 examined L. pneumophila aerosol generation by plumbing in bathrooms, they found very low concentrations (0.27-0.44 CFU m -3 ) of bacteria in the air during the first 15 minutes of showering and no airborne Legionella during 15 and 30 minutes of showering, even though concentrations of L. pneumophila in the water were approximately 10 3 CFU L -3 . At a breathing rate of 12 L min -1 , over 4 hours of showering would be required to inhale just one “viable” Legionella cell (although the researchers likely meant to use the term “culturable” since viable but non-culturable (VBNC) cells were not distinguished in their study).…”
Section: Introductionsupporting
confidence: 79%
“…Bolin (22) Near aerated sink faucets in a hospital 2 to 9 CFU/m 3 > 2 × 10 5 CFU/L Not associated with LD cases. Based on 6 of 19 positive air samples Dennis (21) Near shower heads 0.33 CFU/m 3 10 3 CFU/L Not associated with LD cases Breiman (96) In shower aerosol 190 CFU/m 3…”
Section: Data Source Location Air Concentration Water Concentration Cmentioning
confidence: 99%
“…L. pneumophila has been isolated from aerosols created by water faucets (24), by humidifiers, and by the squeezing of manual ventilation bags (277). Some investigators have been able to demonstrate legionellae in aerosols produced by showers (24,55), but others have been unsuccessful (277). In one study, L. pneumophila was isolated during two successive 15-min periods (24), whereas Dennis and colleagues were able to recover legionellae only during the first sampling period (55).…”
Section: Route Of Infectionmentioning
confidence: 99%
“…Some investigators have been able to demonstrate legionellae in aerosols produced by showers (24,55), but others have been unsuccessful (277). In one study, L. pneumophila was isolated during two successive 15-min periods (24), whereas Dennis and colleagues were able to recover legionellae only during the first sampling period (55). Analysis of aerosols with cascade impingers has shown that the bacteria are contained in droplets that are of respirable size (55).…”
Section: Route Of Infectionmentioning
confidence: 99%
See 1 more Smart Citation